2009
DOI: 10.1007/s11703-009-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of Kentucky bluegrass (Poa pratensis L.) to trinexapac-ethyl applied in spring and autumn

Abstract: The practices with low clippings production to save time, money, or landfill space, were favored by turf managers. Understanding the responses of Kentucky bluegrass (Poa pratensis L.) to Trinexapac-ethyl (TE) would facilitate recommendations regarding its safe and effective use in Northern China. The objectives of this study are (1) to investigate the effects of TE on vertical growth, clipping yield, leaf width, and chlorophyll content of Kentucky bluegrass, and (2) to compare the seasonal application impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Reductions in canopy heights as a result of TE applications were expected because these effects have been detailed in previous reports. Coolseason grass growth reduction by TE has shown by previous researchers (Ervin and Koski, 2001;Fan et al, 2009;Heckman et al, 2005), which are in agreement with the results of this study. The mode of action for TE involves accumulation at the intercalary meristems region, subsequent interference with GA biosynthesis, and reducing cell elongation in leaves (Kaufmann, 1986).…”
Section: Canopy Heightsupporting
confidence: 94%
See 2 more Smart Citations
“…Reductions in canopy heights as a result of TE applications were expected because these effects have been detailed in previous reports. Coolseason grass growth reduction by TE has shown by previous researchers (Ervin and Koski, 2001;Fan et al, 2009;Heckman et al, 2005), which are in agreement with the results of this study. The mode of action for TE involves accumulation at the intercalary meristems region, subsequent interference with GA biosynthesis, and reducing cell elongation in leaves (Kaufmann, 1986).…”
Section: Canopy Heightsupporting
confidence: 94%
“…Furthermore, TE treated plants are mainly associated with shorter internode distances and lower vertical growth as compared to control plants. Fan et al (2009) reported that TE applications in spring and autumn decreased turfgrass growth and reduced mowing frequency. Results from this experiment demonstrated the benefits of sequential applications of TE for inhibition of perennial ryegrass growth.…”
Section: Canopy Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative damage has been proposed to reduce the chlorophyll content (Han et al, 2008), such that accumulation of free radicals during stress may be responsible for the loss of chlorophyll content (Inze and Montagu, 2002). Several investigators have demonstrated that TE treatment increases the chlorophyll content (Ervin and Koski, 2001;Fan et al, 2009). TE has been documented to reduce cell elongation by inhibiting gibberellin synthesis and increase the number of mesophyll cells, cytokinin content, and subsequently the chlorophyll concentration in leaves (Fan et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have demonstrated that TE treatment increases the chlorophyll content (Ervin and Koski, 2001;Fan et al, 2009). TE has been documented to reduce cell elongation by inhibiting gibberellin synthesis and increase the number of mesophyll cells, cytokinin content, and subsequently the chlorophyll concentration in leaves (Fan et al, 2009).…”
Section: Resultsmentioning
confidence: 99%